Development of Keropok Keping Drying Machine for Small & Medium Enterprises (SMEs) - Mohamaddan, Shahrol; Mohd Mohtar, A. M A A; Junaidi, Nazreen; Mohtadzar, Nur Alia Athirah Binti Hj; Mohamad Suffian, Mohamad Syazwan Zafwan (Institute of Physics Publishing, 2016)
Keropok is a traditional cracker product in Southeast Asia. Keropok is made from fish, squid or shrimp mixed with starch or sago flour and eggs. In Malaysia, keropok industry is widely operated at the coastal areas where the fish/seafood supply can be easily accessed. Keropok need to be dried before the packaging process. At the moment, conventional method was used where the keropok is arranged under the sunlight on a board called pemidai. The method is considered less hygienic since it exposed to the dirt and dust and less practical especially during the raining season. This research is focusing on a new automation technique to solve the problems. Rotary drum with internal holder was developed as the drying machine. Keropok keping (types of keropok) was selected to be experimented using the machine with three different rotating speeds. Preliminary experiment result shows that the broken rate of the keropok keping was around 27% of the total weight. The development of new automation system is hoped to improve the small medium enterprises (SMEs) in Malaysia.